Sounds of Identity: The Whistled Language of La Gomera - Loffredo, Samuele (My University, 2018)
The Canary island of La Gomera preserves a particular whistled language, known as El Silbo that was sentenced to disappear by modernity, if it was not for the effort of local government and institutions that have recently acknowledged its cultural significance. In a world were globalization unifies values and cultural models, El Silbo Gomero traces back to the traditional identity of the islanders. While most scientific research around whistled languages appears to be purely linguistic in its nature, the present study aims to explore how the mere existence of the whistled language contributes to shape and construct the identity of locals, intended as a social group, and consequently shed some light on the possible roles that the whistled language can find in modern La Gomera. This qualitative short-term study is underpinned by social identity theory, as it is intended by Tajfel and Turner and more specifically by the concept of acts of identity, which displays the use of language as an act to represent identity. Data is extrapolated from a set of semi-structured qualitative interviews held with four whistlers who had and still have an active and significant role in the initiatives that contribute to the preservation of the Silbo. The interviews’ transcripts are systematically analyzed trough content analysis method. The qualitative content analysis of the semi-structured interviews demonstrates that participants attach to El Silbo both functional utility and symbolic significance. In addition, the whistled language is also used as a mean, or an identity act, to reinforce in-group sense of belonging.
Keywords: Silbo Gomero; whistled language; acts of identity; identity construction; social identity; content analysis.; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|